Til Nordmænd om en Norsk Høi-Skole, 1837. En indledning - Yde, Henrik (Grundtvig-studier, 2012)
Til Nordmænd om en Norsk Høi-Skole. En indledning[To the Norwegians concerning a Norwegian High School. An Introduction]By Henrik Yde To the Norwegians concerning a Norwegian High School (1837) is the second of Grundtvig’s major writings on people’s high schools or national high schools. It is also the only one aimed at a non-Danish public. And whereas his other writings on this subject did not catch much attention in Denmark when published, To the Norwegians concerning a Norwegian High School immediately stirred up a fierce debate in Norway.In 1832—after the liberal revolutions in Paris and elsewhere— Grundtvig clearly stated that he was “no friend of parliaments” but preferred absolute monarchy. However, as parliaments did exist, Grundtvig was of the opinion that the voters as well as the members of parliaments ought to receive national education in their vernacular languages in order to gain sense and knowledge about the common good of their respective nations.When addressing the Norwegians, Grundtvig had to take into account that the Norwegian constitution from 1814 was one of the most liberal of all European constitutions. The Norwegian parliament—the Storting—actually had legislative authority and had shown itself to be strong enough to oppose the Swedish-Norwegian king. This was not the case in Denmark, where provisional advisory assemblies—praised by Grundtvig—had been established in 1831 largely to ward off demands for a constitutional monarchy. However, in To the Norwegians concerning a Norwegian High School, Grundtvig deliberately avoids a direct address to the Storting. He chooses not to talk about the need for national education for the members of the Norwegian parliament. This omission is probably due to the fact that while some of Grundtvig’s Norwegian followers were liberals, some were conservatives: thus, it was crucial for him not to be accused of taking sides in Norwegian politics. Instead, he makes a more general claim about a national education in the mother tongue where the students should learn about the common good of the nation. He hardly mentions the Storting.However, when speaking of education in the mother tongue, Grundtvig entered another area of high tension, namely that of the use of the classical language of Latin at the University of Christiania (Oslo) and in the Norwegian upper secondary schools, the ‘ Latin schools’. And though Grundtvig’s conservative Norwegian friends did not share his hatred of Latin, here he did not hesitate to stress the need for a higher national education in the vernacular language.The reaction was immediate: A week before the official release of To the Norwegians concerning a Norwegian High School (on July 29th 1837) the conservative paper Den Constitutionelle (The Constitutionalist) strongly attacked Grundtvig, claiming that his idea of national education was subversive and socialist and also that it was contradictory to his former biblical fundamentalism.These arguments were immediately refuted by the liberal Morgenbladet (The Morning Daily), in which the critic totally agreed with Grundtvig to an extent not even uttered in To the Norwegians concerning a Norwegian High School itself: that a national high school using the mother tongue would be an excellent means for educating the members of the Storting, especially those who had not attended the ‘ Latin school’ in their youth.One specific paper did not react in the first round of the debate: Statsborgeren (The Nationalf), a radical liberal and national paper, edited by the writer Henrik Wergeland. He and Grundtvig had very similar ideas about a number of issues including the enlightenment of the people. However, no dialogue was possible: Wergeland was a liberal applauding the ideals of The French Revolution, Grundtvig was a conservative anti-rationalist. Furthermore Wergeland still remembered that his father Nicolai had had a fierce fight with Grundtvig in the years 1811-16 over Denmark’s political and economic relationship to Norway through the centuries, as being either imperialistic (N. Wergeland’s claim) or altruistic (Grundtvig’s claim). Later, in the debate about To the Norwegians concerning a Norwegian High School, Wergeland attacked Grundtvig along with his Norwegian followers, claiming that Grundtvig was ignorant in the matter of science and a megalomaniac as a person.Thus with the exception of Morgenbladet, the premise of Grundtvig’s booklet was not well understood. Instead, it was considered to be a comment on the standing debate in Norway over the use of Latin at the university and in the upper secondary school.On the sidelines, though, some of Grundtvig’s closest followers in Norway, the wealthy Solem-family, continued to work on their own initiative and with their own money to bring about a Grundtvigian national high school. However, the conditions for this were not yet favourable, either in Norway or in Denmark, and the first Norwegian people’s high school only opened in 1864.